PENATALAKSANAAN FISIOTERAPI DENGAN SHORTWAVE DIATHERMY DAN TERAPI LATIHAN PADA FROZEN SHOULDER DEXTRA ET CAUSA TENDINITIS SUPRASPINATUS - Wardana, Niko Rahma; Purnomo, Didik (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Frozen shoulder associated with supraspinatus tendinitis leads to pain and restricted range of motion, resulting in impaired functional activities. Physiotherapy interventions such as Short Wave Diathermy (SWD) and exercise therapy are required to manage this condition. Objective: To evaluate the effectiveness of combined Short Wave Diathermy and exercise therapy in a patient with right frozen shoulder due to supraspinatus tendinitis. Methods: A case study involving a 60-year-old female patient at Sunan Kalijaga General Hospital, Demak. The intervention consisted of SWD and active exercise therapy over four sessions. Outcomes included pain (VAS), muscle spasm, range of motion (ROM), muscle strength (MMT), and functional ability (SPADI). Results: After four sessions, movement pain decreased from 5 to 2, tenderness from 3 to 1, and muscle spasm resolved. ROM improved, particularly abduction (90° to 110°), and muscle strength increased (MMT from 3 to 4). SPADI scores indicated functional improvement. Conclusion: The combination of SWD and exercise therapy effectively reduced pain and muscle spasm while improving ROM, muscle strength, and functional outcomes in frozen shoulder due to supraspinatus tendinitis